2014
DOI: 10.35196/rfm.2014.3.261
|View full text |Cite
|
Sign up to set email alerts
|

Dinámica Nutrimental Y Rendimiento De Pepino Cultivado en Hidroponía Con Y Sin Recirculación De La Solución Nutritiva

Abstract: Un problema frecuente en los sistemas hidropónicos en los que se recircula la solución nutritiva (sistemas cerrados) es un menor rendimiento y calidad respecto a los sistemas sin recirculación (abiertos), lo cual es atribuido a que las soluciones nutritivas se desequilibran conforme se desarrolla el cultivo, a la vez que se incrementa el riesgo de diseminación de enfermedades. El objetivo de la investigación fue evaluar la factibilidad de sistemas hidropónicos cerrados para alcanzar rendimientos de pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…No statistical difference was found in the number of fruits per plant due to application of phytohormones in all treatments. Sánchez del Castillo et al (2014) reported 38.5 fruits m 2 in Alcázar cultivar with a density of 6 plants m 2 grown in a greenhouse in different hydroponic systems. Golabadi et al (2013) reported that the number of cucumber fruits per plant projects the greatest positive effect on the total production, indicating that this parameter is one of the most reliable components for selecting genotypes with high fruit yield.…”
Section: Number Of Fruitsmentioning
confidence: 99%
“…No statistical difference was found in the number of fruits per plant due to application of phytohormones in all treatments. Sánchez del Castillo et al (2014) reported 38.5 fruits m 2 in Alcázar cultivar with a density of 6 plants m 2 grown in a greenhouse in different hydroponic systems. Golabadi et al (2013) reported that the number of cucumber fruits per plant projects the greatest positive effect on the total production, indicating that this parameter is one of the most reliable components for selecting genotypes with high fruit yield.…”
Section: Number Of Fruitsmentioning
confidence: 99%
“…The crop medium of this systems can consist of only water or different substrates -such as minerals, wool, coconut fiber, or perlite-, with a nutrient solution that provides adequate nutrition (Kratky, 2005;Jones, 2016). In addition, Sánchez del Castillo (2014) indicates that hydroponic systems allow high crop densities, an adequate balance of nutrients, and water savings. For example, the density of strawberry plants grown in open field cultivation systems is 6.5 to 8 plants m 2 , while the planting density in vertical hydroponic greenhouse system can be increased up to three times (Ozeker et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Ante esta problemática, es indispensable buscar sistemas alternativos para la producción de chile poblano, uno de ellos es la hidroponía que se caracteriza por no requerir de suelo como sistema biótico y de sostén para las plantas y ofrece la posibilidad de obtener altos rendimientos (Velasco et al, 2011;Sánchez-del-Castillo et al, 2014). En el sistema hidropónico se suministran los nutrientes que las plantas demandan a través de una solución nutritiva, una de las soluciones más empleadas para la producción de Capsicum annuum es la solución nutritiva formulada por Steiner (Beltrán-Morales et al, 2016;Luna-Fletes et al, 2018;San Juan et al, 2019) dicha solución, debe tener la concentración de nutrimentos adecuada pues de ello dependerá el rendimiento y calidad de los frutos (San Juan et al, 2019).…”
Section: Introductionunclassified